Impact of Coloured LED lights and Lunar Phase on Catches of Selected Shrimp Species in a Filtration Field at Kudappuram, Vembanad Lake - MOHANAN, SALINI; Madhu V. R.; Manoj Kumar B.; Nafin K. S.; Soumya K. R. (Fishery Technology, 2023)
This study examined the influence of using LED lights and moon phase on shrimp caught in filtration field with respect to three shrimp species; Metapenaeus dobsoni, Metapenaeus monoceros and Fenneropenaeus indicus. A total of 849 kg of shrimp comprising three species were collected during the six months (60 trials) of study period from January 2022 to June 2022. The results revealed a significant difference in catch between red light (474.05 kg) and green light (375.40 kg) (LR Chisq = 4.902, df=1, p < 0.05). Shrimps caught using red light (15.8 ± 7.27 kg/ sampling) were significantly higher compared to those caught under green light (12.5 ± 8.84 kg/ sampling). Moon phase also significantly affected total shrimp catch per day (LR Chisq = 20.016, df = 5, p < 0.01). Pairwise comparisons indicated significant differences in catch quantities between specific moon phase combinations. It was found that there was significant difference in catch of M. dobsoni in different moon phase. (LR Chisq = 12.103, df=5, p < 0.05). The catch of M. monoceros were higher under red light than green light, and moon phase significantly affected catches (LR Chisq = 18.319, df=5, p < 0.01). The catch quantities of F. indicus showed no significant difference associated with lighting conditions or moon phase. These findings emphasize the importance of considering lighting conditions and moon phase when assessing shrimp catch, from filtration fields as they can influence catch outcomes which may be due to increased visibility or changes in species behaviour.